2003
DOI: 10.1002/elps.200390106
|View full text |Cite
|
Sign up to set email alerts
|

Insoluble eggshell matrix proteins – their peptide mapping and partial characterization by capillary electrophoresis and high‐performance liquid chromatography

Abstract: Avian eggshell matrix proteins were studied by two analytical approaches. Peptide mapping was done by trypsin and pepsin followed by collagenase cleavage; analyses were carried out by capillary electrophoresis and reversed-phase high-performance liquid chromatography (HPLC). Comparison of peptide maps obtained by both methods revealed a complex mixture of peptides in the insoluble layers of the eggshell; it was concluded that there are at least three different insoluble protein/peptide layers in the avian eggs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 27 publications
(20 reference statements)
1
14
0
Order By: Relevance
“…Both techniques, coupling to a solid support (controlled pore glass), and cross-linking reaction without any solid support, confirmed the advantages of application of immobilized enzymes for peptide mapping: high stability and high activity of the enzyme and noncontamination of protein maps by enzyme fragments due to the suppressed autolysis. CZE and HPLC peptide mapping have been used for characterization of insoluble avian eggshell matrix proteins; better CZE separation and higher number of resolved peaks were obtained in FS capillary dynamically coated with the triblock copolymer Pluronic F127 [77] than in the bare FS capillary [283]. In some advanced systems, CE and CEC peptide mapping is online connected with previous protein digestion by enzymes (trypsin, pepsin) immobilized in microreactors directly coupled to separation capillary [68][69][70].…”
Section: Peptide Mappingmentioning
confidence: 99%
“…Both techniques, coupling to a solid support (controlled pore glass), and cross-linking reaction without any solid support, confirmed the advantages of application of immobilized enzymes for peptide mapping: high stability and high activity of the enzyme and noncontamination of protein maps by enzyme fragments due to the suppressed autolysis. CZE and HPLC peptide mapping have been used for characterization of insoluble avian eggshell matrix proteins; better CZE separation and higher number of resolved peaks were obtained in FS capillary dynamically coated with the triblock copolymer Pluronic F127 [77] than in the bare FS capillary [283]. In some advanced systems, CE and CEC peptide mapping is online connected with previous protein digestion by enzymes (trypsin, pepsin) immobilized in microreactors directly coupled to separation capillary [68][69][70].…”
Section: Peptide Mappingmentioning
confidence: 99%
“…For example in the previous paper [11] we concluded that in all three layers of the eggshell matrix none of the currently described soluble proteins from the eggshell were present. When we look at the peptide profiles, particularly at the molecular mass of the peptides arising after trypsin cleavage, we found a few peptides the molecular mass of which was identical with peptide fragments of soluble eggshell's ovocleidin 116 [12]; on the other hand some peptides had a similar molecular mass of the peptides/proteins of completely different origin as is, e.g., bovine serum albumin.…”
Section: Introductionmentioning
confidence: 92%
“…Proteins from avian eggshells have been studied mainly during the last decade, however, these studies were limited to the soluble species only. Recently [11] we made the first attempt to analyze the insoluble protein/peptide-based constituents of the eggshell matrix by capillary electrophoresis and HPLC/MS. It was proven that these matrices are really complex mixtures of proteins/peptides, some of which are glycosylated.…”
Section: Introductionmentioning
confidence: 99%
“…CZE helped in characterizing insoluble eggshell matrix proteins [270], ribosomoal proteins in Escherichia coli [117], human antithrombin glycoisoforms [271], thaumatin [272], human complement protein C4 [273], intact yeast proteins [162], and identified microbial mixtures based on their marker proteins [274].…”
Section: Other Proteinsmentioning
confidence: 99%